Anxiety Caused by Too Many Cats in Bohumil Hrabalâ€™s â€œAll My Catsâ€ - Teggin, Edward Owen; Harini, Yostiani Noor Asmi (OKARA: Jurnal Bahasa dan Sastra, 2023)
All My Cats is an autobiographical novel representing Hrabalâ€™s fatal anxiety from the potential mental conflict with domesticated animals. This article examines the concept of anxiety and the potential for domesticated animals, in this example, cats, to exert agency and impact the lives of their owners in autobiographical literature. Bohumil Hrabal's All My Cats has been selected due to the prominence of literary signifiers of anxiety, his ambivalent attitude toward cats (love and hate) throughout the text, and Hrabalâ€™s specific interpretation of what his cats did for him and to him in emotional terms. The methodology selected does not presuppose that cats, or animals in the broader sense, possess agency on an equal footing with humans. Rather, they can exist in an interdependent or collaborative state with humans. This may be seen as a form of an unwritten social contract between animals and humans in a domestic setting. In the case of Hrabal and his cats, his perception of his cats and what they attempt to communicate to him is most interesting in this regard, particularly when viewed through the lens of anxiety and the literary signifier.